2018
DOI: 10.1093/climsys/dzy010
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal patterns of daily Indian summer monsoon rainfall

Abstract: The primary objective of this paper is to analyze a set of canonical spatial patterns that approximate the daily rainfall across the Indian region, as identified in the companion paper where we developed a discrete representation of the Indian summer monsoon rainfall using state variables with spatio-temporal coherence maintained using a Markov Random Field prior. In particular, we use these spatio-temporal patterns to study the variation of rainfall during the monsoon season. Firstly, the ten patterns are div… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…These patterns were identified from only 8 years (2000-2007) but they fit well on daily data from over a hundred years. In a companion paper, [17] we will discuss the temporal characteristics of these patterns, showing that some of them to be more frequent in the early and late monsoon months (June, September) while the others are more frequent in the peak monsoon months (July, August), and also study about homogeneous zones on the landmass which are also identified by this model.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…These patterns were identified from only 8 years (2000-2007) but they fit well on daily data from over a hundred years. In a companion paper, [17] we will discuss the temporal characteristics of these patterns, showing that some of them to be more frequent in the early and late monsoon months (June, September) while the others are more frequent in the peak monsoon months (July, August), and also study about homogeneous zones on the landmass which are also identified by this model.…”
Section: Resultsmentioning
confidence: 94%
“…The patterns we identify, and the sequence of their occurrence, provide an ideal platform to understand many features of the monsoon, and we make a beginning in the companion paper [17]. In that paper we collate the results of this paper, i.e., the spatial and temporal patterns, and thoroughly analyze various aspects of these patterns.…”
Section: A Summary Of Our Approach and The Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While they differ in detail from our rainfall patterns, we see broad similarity in that the eight MISO phases too broadly fall into the three “families” (similar to those found by Mitra et al . (2019)) – (a) where the rainfall is restricted to the western coast and the north‐eastern regions, (b) rainfall covers central India, (c) rainfall covers eastern India and the Gangetic plains. By counting the pattern assignments from our method in a particular phase of MISO, we find that each pattern roughly overlaps with 3 MISO phases, generally from the same “family”.…”
Section: Spatial Patterns Of Olr and Rainfallmentioning
confidence: 99%
“…The model then partitions the dataset into spatial and temporal clusters that maintain spatio-temporal coherence. Mitra et al (2019) identified temporal relationships between the patterns corresponding to each cluster. The number of clusters is estimated implicitly by the model and studying the corresponding patterns allows new physical insights to be inferred.…”
Section: Introductionmentioning
confidence: 99%